2019
DOI: 10.1111/ffe.13125
|View full text |Cite
|
Sign up to set email alerts
|

Influence of mode mixity and loading conditions on the fatigue crack growth behaviour of an epoxy adhesive

Abstract: Adhesive joints usually experience mixed mode and mostly cyclic stresses conditions during their service life. The aim of the current research is to investigate the fatigue behaviour of a structural epoxy adhesive. Pure modes I and II and mixed mode tests were carried out to study the fracture and fatigue crack growth (FCG) behaviour of the adhesive. Compliance‐based beam method was considered for experimental fracture energy measurement. The effects of load level and load ratio on the mode I FCG behaviour and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 21 publications
2
11
0
Order By: Relevance
“…One important parameter which should be considered is the threshold fracture energy (G th ), which is defined as the energy release rate below which the fatigue crack growth is negligible. Based on the previous results already published by the current authors, 10 it was shown that for adhesive A, G th in mode I is higher than mode II as shown in Table 3. This associated with the fact that the energy introduced in the system per cycle increases with the presence of a shear component, aggravates the reduction of the fatigue strength as the load angle increases.…”
Section: Influence Of Mode Mixitysupporting
confidence: 67%
See 2 more Smart Citations
“…One important parameter which should be considered is the threshold fracture energy (G th ), which is defined as the energy release rate below which the fatigue crack growth is negligible. Based on the previous results already published by the current authors, 10 it was shown that for adhesive A, G th in mode I is higher than mode II as shown in Table 3. This associated with the fact that the energy introduced in the system per cycle increases with the presence of a shear component, aggravates the reduction of the fatigue strength as the load angle increases.…”
Section: Influence Of Mode Mixitysupporting
confidence: 67%
“…A reason can be the stiffness of the joint that is lower for adhesive B and as stated previously, this affects the introduced energy per cycle. According to previous studies, 10,26 the threshold fracture energy obtained for adhesive A is higher than the one obtained for adhesive B as presented in Table 3. These two factors associated may be the cause for a lower fatigue resistance.…”
Section: Effect Of Adhesive Systemmentioning
confidence: 59%
See 1 more Smart Citation
“…Generally, the total fatigue failure of an adhesive‐bonded joint consists of crack initiation 16,17 and subsequent crack growth 18–21 . It has been reported that the proportion of crack growth life will increase with increasing load levels 22–24 .…”
Section: Introductionmentioning
confidence: 99%
“…One of the reasons is the complexity of loading conditions in adhesive‐bonded joints. Most adhesives are under multiaxial stress conditions 21 in practice, for example, peel, shear and axial stresses in the adhesive layer, even for the simplest single lap joint, 29 which bring challenges to growth life estimation. Furthermore, the crack initiation phase was omitted in these research studies, which would lead to conservative predicted results 30 .…”
Section: Introductionmentioning
confidence: 99%